Kualitas Pelayanan dan Lokasi Pelayanan terhadap Kepuasan Masyarakat - Efendi, Ruslan; Kristiana, Tresia; Sion, Holten (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this research is to analyze and describe the influence of Service Quality on community satisfaction at the Nanga Bulik Village Office, to analyze and describe the influence of Service Location on community satisfaction at the Nanga Bulik District Office, to analyze and describe the influence of Service Quality and Service Location simultaneously on Community Satisfaction Nanga Bulik Village. The data collection techniques used were interviews, questionnaires, observation, and literature study; a sample of 80 people was taken, and the data analysis technique was brilliant PLS version 3. The results of this research show that there is an influence of Service Quality on Community Satisfaction in the Nanga Bulik sub-district; the meaning is Every time there is an increase of 1 () unit in Service Quality, it can be predicted that there will be an increase in public satisfaction of 0.470. There is an influence of Service Location on Community Satisfaction in the Nanga Bulik sub-district, meaning that every time there is an increase of 1 () unit in the service location, it can be predicted that there will be an increase in community satisfaction of 0.388. Service quality and service location influence community satisfaction in the Nanga Bulik sub-district. In conclusion, every time there is an increase in service quality and location, community satisfaction in Nanga Bulik Village will increase. Keywords: Service Quality, Service Location, Community Satisfaction